Exchange Rates, Import Costs, and Wage-Price Dynamics - Bruno, Michael (Journal of Political Economy, 1978)
The study analyzes the wage and price adjustment process in open economies in response to changes in exchange rates and import price. It distinguishes between the impact or cost-push effect, in which the system may exhibit temporary nonneutrality, and the lagged response of excess demand in labor and home-goods markets, which determines the stability of neutrality of long-run equilibria. An empirical illustration is given of the importance of the cost-push effect in explaining differential price behavior of OECD countries during 1972-76.